Inhibitory effects of pentoxifylline on inflammation-related tumorigenesis in rat colon - Shirakami, Yohei (Oncotarget, 2018)
Chronic inflammation in the colorectum increases the risk of colorectal cancer development. Pentoxifylline, a medicine used for improving the circulation, has been reported to inhibit TNF-α production and to ameliorate inflammatory bowel disease and non-alcoholic steatohepatitis. In this study, we investigated the effects of pentoxifylline on inflammation-related colon tumorigenesis in a rodent model using Kyoto APC delta rats, which have APC mutation and are susceptible to colon carcinogenesis. Male Kyoto APC delta rats were treated with azoxymethane and dextran sodium sulfate, and were subsequently administered water, with or without pentoxifylline. At the end of the experiment, the development of colorectal tumor was significantly inhibited in the pentoxifylline group. The pentoxifylline treatment also lowered the levels of oxidative stress markers and mRNAs of pro-inflammatory cytokines, including TNF-α and IL-6, in the colon mucosa. The PCNA labeling index and the inflammation score were also decreased in the colon of rats in the pentoxifylline -treated group. We also used an endoscopy to observe the tumor progression and inflammation in the colon of rats, revealing that inflammation grade was significantly lower in pentoxifylline-treated group at several points during the experiment. These findings suggest that pentoxifylline treatment might be useful for chemoprevention of inflammation-related colon cancer.